1999
DOI: 10.1002/(sici)1096-9861(19991129)414:4<495::aid-cne6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the axotomy to cell body distance in rat rubrospinal and spinal motoneurons: Differential regulation of GAP-43, tubulins, and neurofilament-M

Abstract: Axotomized motoneurons regenerate their axons regardless of whether axotomy occurs proximally or distally from their cell bodies. In contrast, regeneration of rubrospinal axons into peripheral nerve grafts has been detected after cervical but not after thoracic injury of the rubrospinal tract. By using in situ hybridization (ISH) combined with reliable retrograde tracing methods, we compared regeneration‐associated gene expression after proximal and distal axotomy in spinal motoneurons versus rubrospinal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 76 publications
6
129
1
Order By: Relevance
“…Proximal axotomies are linked to altered expression of growth-associated proteins such as GAP-43, ␣-tubulins, and neurofilament-m (Fernandes et al, 1999) and are associated with increased axonal growth capacity . We have previously shown that PCIs are proximally axotomized and express GAP-43 after a midline lesion (Fenrich et al, 2007).…”
Section: Regeneration Despite Inhibitionmentioning
confidence: 99%
“…Proximal axotomies are linked to altered expression of growth-associated proteins such as GAP-43, ␣-tubulins, and neurofilament-m (Fernandes et al, 1999) and are associated with increased axonal growth capacity . We have previously shown that PCIs are proximally axotomized and express GAP-43 after a midline lesion (Fenrich et al, 2007).…”
Section: Regeneration Despite Inhibitionmentioning
confidence: 99%
“…There are several possible reasons for this disparity: first, manipulations associated with DRG dissociation and microinjection render the transplanted neurons less susceptible to inhibitory factors present in the degenerating dorsal columns; second, the different regenerative responses might relate to the amount of axon lost (in the Davies experiments all of the axon was removed). In several systems the regenerative response is augmented with increasing proximity of the lesion to the cell body (Mathew and Miller 1993;Fernandes et al, 1999). Other differences may include the differing glial elements encountered by regenerating axons along their course (after rhizotomy for example, axons must transit from Schwann cells to astrocytes), or temporal aspects: with delayed treatment, the axons would have been stopped for several days, possibly altering the extent to which they are capable of responding to NT-3 (although the equivalent upregulation of GAP-43 in immediately and belatedly treated rats would suggest otherwise).…”
Section: Barrier Two: Frank Degenerationmentioning
confidence: 99%
“…Although axotomy close to the cell body can produce a more robust (2,10,19,45) or faster (45) regenerative response, this is doubtful in the present study. The distance to the cell body is not as different between the two conditions as it might first seem.…”
Section: What Accounts For State-dependent Axonal Growth Plasticity?mentioning
confidence: 61%